Incorporating traditional and emerging biomarkers in the clinical management of metastatic colorectal cancer: an update. (2nd July 2020) - Baraibar, Iosune; Ros, Javier; Mulet, Nuria; Salvà, Francesc; Argilés, Guillem; Martini, Giulia; Cuadra, José Luis; Sardo, Emilia; Ciardiello, Davide; Tabernero, Josep; Élez, Elena
ABSTRACT: Introduction: Molecular profiling has led to significantly longer survival in metastatic colorectal cancer (mCRC) patients. Clinical guidelines recommend testing for KRAS/NRAS, BRAF and MSI status, and new biomarkers such as HER2 amplification and NTRK fusions have emerged more recently in refractory CRC, supported by overwhelming clinical relevance. These biomarkers can guide treatment management to improve clinical outcomes in these patients. Areas covered: Preclinical and clinical data over the last decade were reviewed for known and novel biomarkers with clinical implications in refractory CRC. Molecular alterations are described for classic and novel biomarkers, and data for completed and ongoing studies with targeted and immunotherapies are presented. Expert opinion: Use of targeted therapies based on biomarker testing in CRC has enabled impressive improvements in clinical outcomes in refractory patients. BRAF, MSI, NRAS and KRAS should be tested upfront in all patients given their indisputable therapeutic implications. Other molecular alterations such as HER2 and NTRK are emerging. Testing for these alterations may further improve outcomes for refractory CRC patients. Nonetheless, many key aspects remain to be defined including the optimal timing and technique for testing, the most adequate panel, and whether all patients should be tested for all alterations.